INFLUENCE OF THE PARTICLE SIZE OF CATALYST ON THE HYDROCRACKING OF VACUUM DISTILLATE INTO MIDDLE DISTILLATE AND LUBRICANT BASE STOCK - A.S. Nasution (Scientific Contributions Oil and Gas, 1985)
In order to obtain more data on the hydrocracking catalysts, an experiment has been carried out to study the hydrocracking of vacuum distillate into middle distillate with operating conditions: temperature: From 390 to 420°C: LHSV: from 0.45 to 0.90;  presRure: 125 kg/cm and HHC ratio: 1000 It/lt by using Two Ni-Mo/Al 03 SIO, catalysts with various particle stzes using a Catatest unit operated in a continuous sys- tem.Gas product sample was analyzed by using a gas-liquid chromatography, The liquid product were fractionated and bottom products were dewaxed by solvent dewaxing.Based on the experimental data show that :By increasing the operating temperature, LHSV, and decreasing of the particle size of the Ni-Mo/Al0Si0, cutalyst, the conversion rate, the quality of the middle distillate, and the lubricant base stocks products in  - crease, but the selectivity of these products will decrease.At operating conditions T= 400°C, P-125 kg/cm;  LHSV = 0.45;  and H/HC ratio : 1000 It/lt, the conversion rate, smoke point of kerosene, diesel index of gas oll, viscosity index of lubricant base stock decrease from: 54.08 to 50.08% by weight;  from 22 to 16 mm, from 62.0 to 57.7 and from 133 to 118 for the low particle size and high particle size of the Ni-Mo/Al 0rSiO, catalysts respectively.  The apparent activation energy of vacuum distillate is obtained 28,717 and 23,720 kcal/mol for the low par ticle size and the high particle size of the Ni-Mo/Al-0SIO2 catalyst respectively.